Kajian Potensi Air Pengerak Pompa Hidram untuk Mengairi Sawah di Daerah Pakandangan Kabupaten Padang Pariaman - Ichlas Nur; Nota Effiandi; . Mulyadi; . Maimuzar; . Hendra (Jurnal Ilmiah Poli Rekayasa, 2019)
Energy is needed in mobilizing a mechanism both electric energy and energy derived from fossils. Hydram pump is a device to raise water from a low place to a high place by utilizing water impacts without using renewable energy. In Pakandangan, Padang Pariaman Regency, there is a water source that cannot be utilized to flow through the rice fields around 10 Ha. Because the rice fields are higher with water sources. The methodology is to survey the location and design the dimensions of the hydram pump. The results obtained head data height of incoming water is 2.5 meters, the height of water lift to the shelter is 7 meters the flow of water entering the pump is 25 lt / sec. The dimensions of the pump are the result of the design of a hydram 1 size with an inside diameter of 2 inches